PERBANDINGAN ANTARA ALANTOIN (5 UREIDOHYDANTOIN) DENGAN BETADINE® (POVIDONE IODINE) UNTUK PENGOBATAN LUKA BVSISI - Didik Tulus Subekti (Research Center for Biology-Indonesian Institute of Sciences, 1998)
Study on the comparison between allantoin (5 ¢ ureidohydantoin) and Betadine ® (povidone iodine) was conducted to compare and evaluate their efficacy, especially to accelerate wound (incision) healing. Treatment divided into three groups, first group is Control (without therapy), second group is allantoin treatment and the last one is Betadine ® treatment. Allantoin obtained from cattle's urine by Meissner method. The solution made of 2,4 grams of allantoin in 600 milliliters aqueous solution. Treatments (therapies) were given three times a day topically. Results showed no significant difference between allantoin and Betadine ® treatments (p > 0,05), control and the other treatments i.e allantoin and Betadine ® therapies have significantly difference (p < 0,01).